+0  
 
0
36
1
avatar

What transformations are used for y=1/x to become 6y=-3/x?

 Jan 23, 2019
 #1
avatar+95884 
+1

y = 1 /x

 

6y = -3 /x  ⇒  y  = (-3/6x)  ⇒  y = (-1/2)(1/x)

 

This "flips"  (1/x)  across the x  axis  and  vertically compresses 1/x  by a factor of 1/2

 

 

cool cool cool

 Jan 23, 2019

9 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.